Risk Factors in ERP Implementation Projects for Process Oriented - Andrzej Partyka (Contemporary Economics)
This paper present review and analysis of risk factors, which could affect successful implementation of ERP system, for project performed in project oriented organizations. Presented risk breakdown structure and the list of common risk factors, are well-suited for ERP implementation projects. Considered risk categories allow for complex risk analysis. Additionally, mapping of risk importance for particular implementation phases is presented. Making presented model an important input for project risk management process, especially for the beginning phases which require identification of risk factors.